2016
DOI: 10.3847/0004-637x/825/1/71
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Evolution of Mass-Transferring Eccentric Binary Systems. Ii. Secular Evolution

Abstract: Finite eccentricities in mass-transferring eccentric binary systems can be explained by taking into account mass-loss and mass-transfer processes that often occur in these systems. These processes can be treated as perturbations to the general two-body problem. The time-evolution equations for the semi-major axis and the eccentricity derived from perturbative methods are in general phasedependent. The osculating semi-major axis and eccentricity change over the orbital timescale and they are not easy to impleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 31 publications
2
53
2
Order By: Relevance
“…Our results show a good agreement with the secular evolution equations derived by Dosopoulou & Kalogera (2016) for fast isotropic winds, as long as the outflow in our models approximates the spherically symmetric wind case. However, when the ouflow morphology is modified by interaction with the binary, our results deviate from the analytical description.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our results show a good agreement with the secular evolution equations derived by Dosopoulou & Kalogera (2016) for fast isotropic winds, as long as the outflow in our models approximates the spherically symmetric wind case. However, when the ouflow morphology is modified by interaction with the binary, our results deviate from the analytical description.…”
Section: Resultssupporting
confidence: 84%
“…In addition to these proposed eccentricity pumping mechanisms, detailed analytical studies of the orbital evolution of eccentric binary systems have been performed by Sepinsky et al (2007b), Sepinsky et al (2009) Eggleton (2006), and Dosopoulou & Kalogera (2016). For instance, Eggleton (2006) and Dosopoulou & Kalogera (2016) derive the secular evolution of the semi-major axis and the eccentricity of an eccentric binary when interaction occurs via fast isotropic winds. However, several hydrodynamical studies have shown that wind interaction in AGB binaries can be quite different from the isotropic-wind mode (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, equation (39b) states that, as e → 0, ė ∝ e, i.e., e decays exponentially to zero. In contrast, according to the delta function model of Sepinsky et al (2007b) and Dosopoulou & Kalogera (2016b), for low eccentricities ė ∝ √ 1 − e 2 (1 − e) ≈ 1 − e, i.e., ė is nonzero at e = 0, and this can lead to undesirable properties (see Section 3 below for explicit examples). This is a consequence of the assumption of a delta function mass transfer rate at periapsis, whereas periapsis is not defined for circular orbits.…”
Section: Assumptions Of the Ejection/accretion Radiimentioning
confidence: 99%
“…Nevertheless, the problem of mass loss/mass transfer has been studied for over half a century (e.g., Huang 1956;Hadjidemetriou 1963;Kruszewski 1964;Piotrowski 1964;Matese & Whitmire 1983, 1984, and has received more recent attention in numerical studies (e.g., Regös et al 2005;Church et al 2009;Sepinsky et al 2010;Lajoie & Sills 2011a,b;van der Helm et al 2016;Bobrick et al 2017), as well as in (semi)analytical work (Sepinsky et al 2007b(Sepinsky et al , 2009(Sepinsky et al , 2010Veras et al 2011;Veras & Tout 2012;Veras et al 2013Veras et al , 2014Dosopoulou & Kalogera 2016a,b). Sepinsky et al (2007b) and Dosopoulou & Kalogera (2016b) in particular derived equations for the secular (i.e., orbit-averaged) changes of the orbital elements due to mass transfer in eccentric binaries. For the case of Roche Lobe overflow (RLOF), they assumed that the mass transfer rate is a delta function centered at periapsis, i.e., the donor star transfers its mass in a burst at its closest approach to its companion.…”
Section: Introductionmentioning
confidence: 99%
“…These mass transfer rates are not unreasonable to assume and we thus proceed with this proof-ofconcept calculation. We note that alternative models exist (Hamers & Dosopoulou 2019;Dosopoulou & Kalogera 2016;Sepinsky et al 2007) that incorporate orbital evolution, and will be included in future work.…”
Section: Mass Transfermentioning
confidence: 99%